PEMAKNAAN KONSEP NRIMO ING PANDUM PADA PEDAGANG TRADISIONAL DI PASAR LEGI SURAKARTA - Mutia, Fatimah; Putri Andari, Nabila; Salsabila Khairunnisa, Nasywa (JURNAL ILMU BUDAYA, 2023)
Nrimo ing pandum is interpreted and applied in the daily life of the Javanese people, one of which is traditional traders that include syukur, sabar, and nrimo, so they can survive in various circumstances that sufficiently change the economic conditions. The formulation of the problem in this study is how to interpret the concept of nrimo ing pandum to traditional traders. This research aims to determine how nrimo ing pandum is analyzed from the perspective of conventional traders in Legi Market, Surakarta. This research is qualitative in the form of a phenomenological study using interviews and literature studies. The study results show that the meaning of nrimo ing pandum is reflected in the attitudes of syukur, sabar, and nrimo, especially when facing unstable economic conditions. This result shows that the concept of nrimo ing pandum is still applied and rooted in the personality of the Javanese people, mainly traditional traders.